Efektifitas Buku Augmented Reality Interaktif untuk Meningkatkan Literasi Lingkungan Anak Sekolah Dasar - Pithaloka, Hanna; Saffira, Mega; Londa, Adela Eltimothy (Paedagogie, 2025)
This study aims to examine the effectiveness of an interactive Augmented Reality (AR) book as a learning medium to enhance environmental literacy among elementary school students. Environmental literacy encompasses the ability to understand, respond to, and act wisely on environmental issues, which should be instilled from an early age. The AR book was developed with educational content themed around the reuse of second-hand clothing as an effort to reduce textile waste, presented through engaging visual and audio elements tailored for children. The research employed a quasi-experimental method with a one-group pretest-posttest design, involving 31 upper-grade elementary students as participants. The instrument used was an environmental literacy test. The results showed an increase in the average score from 13.4 to 13.8 after the intervention. However, statistical analysis revealed a significance value of 0.255, indicating that the improvement was not statistically significant. These findings suggest that while there was a slight increase in students’ average scores, the use of the interactive AR book did not produce a significant impact on their environmental literacy. The study recommends further development of content and more intensive learning approaches to enhance the effectiveness of technology-based media in environmental education.